Zooplankton filtering efficiency of the baleen of a North Atlantic right whale, Eubalaena glacialis - Mayo, C.A.; Letcher, B.H.; Scott, S. (J. Cetacean Res. Manage., 2020)
In order to define the trophic requirements of the North Atlantic right whale, a series of experiments were designed to examine the food capture characteristics of the species. The food filtering efficiency of the baleen of an immature right whale was tested in a flume using graded samples of zooplankton, primarily calanoid copepods, collected in the path of surface-feeding whales. The filtering capacity decreased with decreasing prey organism size, so that greater than 95% of the available caloric content of the zooplankton samples was captured in size fractions collected on 333m mesh nets. The experiments demonstrate that the filtering efficiency of the baleen narrowly focuses the right whale’s feeding on an energy-rich, yet spatially and temporally variable, portion of the mid-water food resource